If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -7x = -61 Solving 2 + -7x = -61 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -7x = -61 + -2 Combine like terms: 2 + -2 = 0 0 + -7x = -61 + -2 -7x = -61 + -2 Combine like terms: -61 + -2 = -63 -7x = -63 Divide each side by '-7'. x = 9 Simplifying x = 9
| 3x^2+14w+8=0 | | 9x^2+6xy+y^2= | | 1.52+2= | | -42+(-55)= | | 2x+3y=135 | | -z+4(x+3)=-12 | | X^2-12x=-x | | 11x-x=14 | | 4b^5+8b+7=4 | | (5x/2)-(5x/6) | | 3s-5t=7t | | -6+9=21 | | 84=4n | | 2x+3.75=7x | | 2x^3-15X^2=2x | | 2x-b+8=5b+4 | | h(x)=2x+4 | | 2532500/x/1277.59=27.68 | | z+2(4+z)=3z+8 | | (3x^4y^3)(9x^2y^6)= | | 10y=2x+5 | | (3-2g)(7-g)=0 | | 2(R+10)=68 | | 15x^3y^11= | | ax+3b=9b | | 0=k-4+4 | | -750c^5+162c^2=0 | | 5x=3x-17 | | 2+6x+2=4 | | (3xy^10)(5x^2y)= | | x+3=8x-4 | | w^2-33w=0 |